Hukum Jual Beli Air Susu Ibu Analisis Pendapat Imam Abu Hanifah dan Imam Malik - Mahfudz, Muhammad Sahal (Al-Mazaahib: Jurnal Perbandingan Hukum, 2022)
In the view of the fuqoha, the practice of buying and selling breast milk is different about whether it is permissible or not. Imam Abu Hanifah is of the opinion that breast milk should not be traded because it includes human flesh. Meanwhile, Imam Malik is of the opinion that breast milk may be traded for sacred reasons. In this case the author uses the library research method-qualitative by using the theory of ta'arud fair and maslahah mursalah. The results of this study determined that the law of buying and selling breast milk both had in common, namely using the qiyas method. In this case, Imam Abu Hanifah sees the buying and selling of breast milk more on the sanctity of objects and the harm that occurs when this sale and purchase is carried out. Meanwhile, Imam Malik sees it from the side of the benefit of goods being traded.